Nonblocking supervisory control of state tree structures - Chuan Ma; Wonham, W.M. (IEEE transactions on automatic control, 2006)
It is well known that the nonblocking supervisory control problem is NP-hard, subject in particular to state space explosion that is exponential in the number of system components. In this paper we propose to manage complexity by organizing the system as a state tree structure (STS). STS are an adaptation of statecharts to supervisory control theory. Based on STS we present an efficient recursive symbolic algorithm that can perform nonblocking supervisory control design (in reasonable time and memory) for systems of state size 10/sup 24/ and higher. The resulting controllers are tractable and readily comprehensible.